COMPARATIVE ESSENTIAL OIL COMPOSITION OF AERIAL PARTS OF MICROMERIA PERSICA POPULATIONS FROM FOUR REGIONS IN FARS PROVINCE, IRAN - Elham NASER KAMJOO; Maryam NASER KAMJOO (Rojan GÜMÜŞ, 2017)
There are three species of the Micromeria plant in Iran, one of which is Micromeria persica. Different species of Micromeria has been used in traditional medicine. The current study deals with identifying chemical compounds of Micromeria persica populations in four regions of Fars province in Iran. These regions are Kuh-e Zireh, Firuzabad, Bezyn defile in Darab and Ghir to Firuzabad. First, the aerial parts of Micromeria persica collected as samples were dried. Then, the essence of the dried samples was extracted by water distillation in the Clevenger machine, and identification of compounds was made using the GC/MS machine. In Kuh-e Zireh, Firuzabad, Bezyn defile in Darab and Ghir to Firuzabad regions, the numbers of recognized compounds were 30, 45, 50 and 25 respectively. The main essence compounds of the four examined populations were Germacrene D, Bicyclogermacrene, spathulenol, and δ-cadinene. Geographical position and ecological parameters of habitat, such as height, annual rainfall, and climate, can change the quality and quantity of the essential oil's compounds in Micromeria persica.